2019
DOI: 10.3389/fpls.2019.00213
|View full text |Cite
|
Sign up to set email alerts
|

Citrus sinensis MYB Transcription Factor CsMYB85 Induce Fruit Juice Sac Lignification Through Interaction With Other CsMYB Transcription Factors

Abstract: Varieties of Citrus are commercially important fruits that are cultivated worldwide and are valued for being highly nutritious and having an appealing flavor. Lignification of citrus fruit juice sacs is a serious physiological disorder that occurs during postharvest storage, for which the underlying transcriptional regulatory mechanisms remain unclear. In this study, we identified and isolated a candidate MYB transcription factor, CsMYB85, that is involved in the regulation of lignin bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 42 publications
(74 reference statements)
1
23
0
Order By: Relevance
“…The levels of lignin, pectin, hemicellulose, and cellulose all increase in granulating fruit juice sacs [14,26]. Especially, the juice sac lignin content increases during granulation and plays a vital role in this process [16,26]. Similar results were obtained in our experiment.…”
Section: Effects Of Winter Low Temperature On Fruit Granulationsupporting
confidence: 90%
See 2 more Smart Citations
“…The levels of lignin, pectin, hemicellulose, and cellulose all increase in granulating fruit juice sacs [14,26]. Especially, the juice sac lignin content increases during granulation and plays a vital role in this process [16,26]. Similar results were obtained in our experiment.…”
Section: Effects Of Winter Low Temperature On Fruit Granulationsupporting
confidence: 90%
“…Puffing mostly alters primary metabolism, such as fatty acid, pentose phosphate, and glyceride [31]. Besides, some other studies have shown that lignin metabolism is closely associated with the process of juice sac granulation [13,14,16,26]. In this study, RNA-sequencing technology was used to further confirm that the fruit granulation of late-ripening navel orange is closely related to cell wall metabolism and the related genes were identified.…”
Section: Gene Expression In Late-ripening Navel Orange Fruit Under Lomentioning
confidence: 78%
See 1 more Smart Citation
“…Previous findings have revealed that TFs play a crucial role in sweet orange granulation. For example, CsMYB330 and CsMYB85, which are homologs of AtMYB58/AtMYB63 and AtMYB85, respectively, have been reported to interact with CsMYB308 through the binding of the Cs4CL1 promoter 10,30 to regulate juice sac granulation.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the expression levels of these genes were at high levels at 60 DFA, but simultaneously dropped to extremely low levels at 90 210 DAF in four pomelos, the key pathway genes might be regulated by some TFs [30]. Numerous TFs have been reported to regulate lignin and anthocyanin biosynthesis in phenylpropanoid pathway [31]. For example, CsMYBF1 was found to bind to CHS-1 promoter and then affect avanone accumulation in citrus [32]; Ruby was found to bind to CHS, DFR and ANS promoters, then regulate anthocyanin accumulation in blood orange and Zipi pomelo [9,33].…”
Section: Introductionmentioning
confidence: 94%